Front and Back Matter for Volume 2 Issue 2, March 2025 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2025)
Volume 2 Issue 2, March 2025This issue consists of 5 articles contributed by 15 authors affiliated with 12 affiliations from four countries, including Indonesia (Universitas Muhammadiyah Surakarta, K.R.M.T. Wongsonegoro Hospital, Universitas Negeri Makassar, Universitas Sawerigading, Universitas Jenderal Soedirman, Universitas Sriwijaya, Universitas Negeri Manado), Afghanistan (Rabia Balkhi Hospital), India (B. J. Medical College, Civil Hospital Campus, Mobile Veterinary Units (MVUs) India, Narayan Consultancy on Veterinary Public Health and Microbiology), and Ethiopia (Sebeta Sub-City Agricultural Office).